Isu Pembubaran Dewan Perwakilan Rakyat Perspektif Hukum Tata Negara dan Hukum Islam tentang Keseimbangan Kekuasaan - Devia Dwi Natasha; Retanisa Rizqi; Aziza Aziz Rahmaningsih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2026)
his research is motivated by the growing public trust crisis toward the Indonesian House of Representatives (DPR) in 2025, which culminated in discourse surrounding the dissolution of the legislative body; an issue that has never been comprehensively examined in Indonesian constitutional law literature and therefore demands urgent scholarly attention. This study aims to analyze the factors underlying the DPR's legitimacy crisis through two theoretical frameworks: David Beetham's legitimacy theory, encompassing the dimensions of legality, normative justification, and public consent, as well as the principles of fiqh siyasah, namely syura (deliberation), amanah (accountability), and hisbah (socio-political oversight), employing a juridical-normative and prescriptive analytical method through library research and documentation. The primary legal materials used include the 1945 Constitution of the Republic of Indonesia, the Law on the People's Consultative Assembly, House of Representatives, and Regional House of Representatives (MD3 Law), and the Qur'an as the primary reference for fiqh siyasah analysis, supported by secondary legal materials comprising legal textbooks, scholarly journals, academic articles, and classical texts related to the principles of syura, amanah, and hisbah, as well as tertiary legal materials in the form of legal dictionaries and language dictionaries. The findings indicate that the crisis stems from the DPR's failure to effectively carry out its legislative, oversight, and budgetary functions, compounded by public dissatisfaction with an institution perceived as insensitive to the hardships faced by the people, and that Article 7C of the 1945 Constitution constitutionally prohibits the dissolution of the DPR, meaning that the restoration of legitimacy can only be pursued through institutional reform and constitutional amendment driven by the will of the people. This research contributes by offering a constitutional legitimacy model that integrates Beetham's theory with the principles of fiqh siyasah as a normative framework to strengthen the checks and balances mechanism and restore public trust in Indonesia's legislative institution.